Evaluación de daños comparativos por insectos en dos plantaciones de Vochysia lomatophylla "quillosisa", CIEFOR - Puerto Almendra. Loreto. Perú. 2019 - Izaguirre Vilcarromero, Elsa Adith (2021)
The study was realized in two plantations of Vochysia lomatophylla "Quillosisa" CIEFOR-Puerto Almendra. The objective was to comparatively evaluate the magnitude of the damage caused by insects in two plantations in Puerto Almendra. The methodology applied was a direct observation, identification, and quantification of the trees and insects found in the two plantations, using the intensity and severity formulas. With the intensity data, 2 families of greater abundance were identified (Termitidae and Formicidae) in plantation 2 with 57.14 % and 35.71 %. On the other hand, plantation 7 with 64.4 % and 27.7 %, respectively. The Severity average in the plantations is a percentage of 33.5% and 47% for the Termitidae family and a percentage of 17.5% and 26.6% for the Formicidae family. Likewise, the magnitude of damage by trees, a category from mild to regular, was obtained with a parameter of 10% - 30%; however, by plantations, there is a severe damage category with an average of 73%.